DAKWAH DIGITAL VIA WHATSAPP: STUDI KASUS REMAJA MASJID TAQWA JANGKAR SITUBONDO - Malik Abdullah; Aminul ‘Alimin (Fakultas Dakwah Universitas Ibrahimy, 2026)
This research is motivated by the radical transformation in the digital communication landscape, where social media has shifted from a mere personal interaction tool to a strategic instrument for disseminating religious teachings (da'wah) in the modern era. This study aims to describe and deeply analyze the utilization of the WhatsApp application as a da'wah medium by the youth members of the Taqwa Mosque in Jangkar Village, Situbondo Regency. The primary focus lies on how this text-and-multimedia-based platform is optimized to maintain the continuity of da'wah at the grassroots level. The research method employed is qualitative with a case study approach. Data collection was conducted through participant observation of the subjects' digital activities, in-depth interviews with key youth mosque leaders, and documentation of the disseminated da'wah content. The findings indicate that WhatsApp serves medium for da'wah content through the Status and Broadcast List features; second, as an internal coordination space (Group Chat) to formulate religious agendas before they are disseminated to the wider community. This study also reveals that the use of WhatsApp carries significant implications covering four main aspects: (1) Social Aspect, namely the strengthening of social cohesion among members; (2) Religious Aspect, in the form of increased digital religious literacy; (3) Psychological Aspect, the growth of self-confidence among youth in preaching; and (4) Technical Aspect, regarding the efficiency of real-time information distribution. In conclusion, WhatsApp is not just a communication tool but a digital sacred space that is effective for mosque youth in maintaining the relevance of da'wah amidst the currents of modernization.